IMPLEMENTASI PELAYANAN PEMBUATAN BUKU PEMILIK KENDARAAN BERMOTOR OLEH SISTEM ADMINISTRASI MANUNGGAL SATU ATAP (Studi Di Kabupaten Landak) - WASHINGTON HASIBUAN NIM. A1011191316 (Jurnal Fatwa Hukum, 2023)
ABSTRACT This study discusses the implementation of vehicle ownership document (BPKB) making service by the One-stop Administration Services Office (SAMSAT) in Ngabang, Landak Regency. Formulation of the problem in this study is the factors that become obstacles in the implementation of vehicle ownership document/BPKB making service at the One-stop Administration Services Office Ngabang and what the efforts were made by the One-stop Administration Services Office at Ngabang, Landak District in the implementation of vehicle ownership document/BPKB service making. Furthermore, the purpose of this study was to find out and analyze implementation vehicle ownership document/BPKB making service in accordance with the provisions or not by the One-stop Administration Services Office in/SAMSAT Ngabang, Landak Regency, secondly to find out and analyze the factors that caused the service making of vehicle ownership document/BPKB by One-stop Administration Services Office/SAMSAT in Ngabang, Landak Regency that is not comply with the provisions, thirdly to find out and analyze the efforts by One-stop Administration Services Office/SAMSAT Ngabang in the Implementation of vehicle ownership document/BPKB Making Services in accordance with the applicable Standard Operating Procedures (SOP). The research method that the author uses in this study is empirical research with an analytical descriptive approach, then the data collection techniques using through field studies and literature studies which include observation, interviews and questionnaires. As for determining the sample of this study using the technique (Purposive Sampling). Furthermore, the method used in this research is qualitative analysis.The results of this study indicate that the services carried out by One-stop Administration Services Office/SAMSAT Ngabang, Landak Regency are not in accordance with Standard Operating Procedures (SOP) caused by the lack of capability of personnel from the Police station in Landak and the issuance of vehicle ownership document which are still concentrated in the West Kalimantan Regional Police office. Preliminary research conducted by researchers from January to September 2022 showing that the average number of people who make vehicle ownership document/BPKB in One-stop Administration Services Office/SAMSAT Ngabang, Landak Regency is 53 (fifty three) people. Making the vehicle ownership document/BPKB in One-stop Administration Services Office Ngabang, Landak Regency took about 3 (three) months while the Standard Operating Procedures/SOP regulating that the making of vehicle ownership document/BPKB only takes ± 40 minutes. The implementation vehicle ownership document/BPKB making service is not accordance with Standard Operating Procedures (SOP). Implementation of Standard Operating Procedures (SOP) has not been effectively implemented.Keyword: Legal Effectiveness, Making vehicle ownership document, Public Service.  ABSTRAK Penelitian ini membahas tentang Implementasi Pelayanan Pembuatan Buku Pemilik Kendaraan Bermotor (BPKB) oleh Sistem Administrasi Manunggal Satu Atap (SAMSAT) Ngabang, Kabupaten Landak. Adapun rumusan masalah dalam penelitian ini yaitu Faktor-faktor yang menjadi kendala dalam Implementasi Pelayanan Pembuatan BPKB di SAMSAT Ngabang dan Upaya apa yang dilakukan SAMSAT Ngabang, Kabupaten Landak dalam Implementasi Pelayanan Pembuatan BPKB. Selanjutnya tujuan penelitian ini adalah untuk mengetahui dan menganalisis pelaksanaan pelayanan pembuatan BPKB sudah sesuai dengan ketentuan atau belum oleh SAMSAT di Ngabang, Kabupaten Landak, kedua untuk mengetahui dan menganalisis faktor-faktor yang menyebabkan pelayanan pembuatan BPKB oleh SAMSAT di Ngabang, Kabupaten Landak tidak sesuai ketentuan, ketiga untuk mengetahui dan menganalisis upaya yang dilakukan oleh SAMSAT Ngabang dalam Implementasi Pelayanan Pembuatan BPKB agar sesuai dengan Standar Operasional Prosedur (SOP) yang berlaku. Metode penelitian yang Penulis gunakan dalam penelitian ini menggunakan jenis penelitian empiris pendekatan Deskriptif Analitis kemudian teknik pengumpulan data melalui studi lapangan dan studi kepustakaan yang meliputi observasi, wawancara dan penyebaran angket. Adapun dalam penentuan sampel penelitian ini menggunakan teknik (Purposive Sampling). Selanjutnya, metode yang digunakan dalam penelitian ini adalah analisis kualitatif. Hasil Penelitian ini menunjukkan bahwa pelayanan yang dilakukan oleh SAMSAT Ngabang, Kabupaten Landak belum sesuai dengan Standart Operasional Prosedur (SOP) dikarenakan kurangnya kemampuan personil anggota Polri Polres Landak dan pencetakkan BPKB masih terpusat di Polda Kalimantan Barat. Penelitian awal yang dilakukan oleh peneliti yaitu sejak bulan Januari sampai dengan bulan Agustus tahun 2022 rata rata jumlah masyarakat yang membuat BPKB di Samsat Ngabang Kabupaten Landak berjumlah 53 (lima puluh tiga) Orang. Pembuatan BPKB di Samsat Ngabang, Kabupaten Landak menghabiskan waktu sekitar 3 (tiga) bulan sedangkan SOP mengatur pembuatan BPKB hanya memakan waktu ± 40 menit. Pelaksanaan pembuatan BPKB tidak sesuai dengan Standar Operasional Prosedur (SOP). Penerapan Standar Operasional Prosedur (SOP) belum efektif diterapkan.  Kata Kunci : Efektivitas Hukum, Pembuatan BPKB, Pelayanan Publik.